Estudo de usuários da Biblioteca Setorial do Instituto de Natureza e Cultura (INC) - Pinto, Francisca da Silva (2016)
The theme "user studies" is a traditional discussion in the field of library science, as it represents a tool that helps in the management of libraries and allows to know the information needs of users. This research fits in as a user study conducted in a university library. The question that guides the research consists in the following proposition: The students library users have met their information needs, and their ethnic and cultural particularities considered the services offered there? The general objective was defined: check the use and satisfaction of users of the Sectorial Library of the Campus of the Institute for Nature and Culture Benjamin Constant as the services offered. Specific objectives include: a) identify the profile of users of the Library's Nature Institute and Campus Culture of Benjamin Constant; b) describe the use of the library by students of the different courses offered at the Campus Benjamin Constant; c) identify the satisfaction of library users about the services offered; d) to analyze the differences in usage and user satisfaction about the library services, considering their cultural and ethnic differences. The research is classified as exploratory and descriptive, presenting a mixed approach (qualitative and quantitative) in which the sample is composed of 137 students coming from six different undergraduate courses. The data collection instrument was a questionnaire consisting of 24 open and closed questions that address the socio-cultural user profile and library usage behavior and its services. It was found the need to modernize the library, in feeling, to provide consistent services with other libraries of federal higher education institutions. In the speech of students, it is the indication and suggestion of the library is computerized and spend the available research processes, renewals, reservations and access via the Internet, as well as investing in the acquisition of assets and equipment such as computers for local use. It was not clear, compared to the survey results, the ethnicity of the students contributes or not to your satisfaction about the services offered in the unit.